Indentation of polyethylene laminates by a flat-bottomed cylindrical punch. (January 2016) - O'Masta, M.R.; Crayton, D.H.; Deshpande, V.S.; Wadley, H.N.G.
Abstract: Cross-ply polymer laminates reinforced by ultra-high molecular weight polyethylene (UHWMPE) fibers and tapes have been subjected to quasi-static indentation by a flat-bottomed, circular cross section punch and their penetration resistance and failure mechanisms investigated. Three fiber- and two tape-reinforced grades progressively failed during indentation via a series of unstable failure events accompanied by substantial load drops. This resulted in a 'saw-tooth' load versus indentation depth profile as the load increased with indentation depth after each failure event. The penetration behavior scaled with the ratio of the thickness of the remaining laminate to the diameter of the punch, and the indentation pressure scaled with the through thickness compressive strength. Failure occurred by ply rupture. The results are consistent with penetration governed by an indirect tension failure mechanism, and with experimental reports that tape-reinforced materials have a similar ballistic resistance to the higher tensile strength fiber-reinforced grades in rear-supported test conditions.